Determining Factors for Mobile Banking Usage Among KBMI 4 Banks: A UTAUT-3 MODEL - Rihan, Raffi Syawallul; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2025)
Digital services and the latest innovations currently emphasize providing increasingly better banking services in line with technological advancements. This study aims to examine the factors driving the adoption of mobile banking and to explore the development of a more specific UTAUT-3 model to identify which factors banks need to improve in order to enhance their services based on users' perspectives. The results of the study, using Structural Equation Modeling (SEM), indicate that Hedonic Motivation, Habit, Facilitating Condition, and Personal Innovativeness are significant predictors influencing users' intention to use mobile banking. Meanwhile, Performance Expectancy, Effort Expectancy, Social Influence, and Price Value do not significantly affect users' intention. These findings can serve as considerations for policymakers in designing strategies to improve payment system services